Momentary equilibrium versus the Wicksell connection - SNIPPE, J. (PSL Quarterly Review, 2013)
The development of monetary economics is closely associated with a possible conflict between the explanation of relative prices by means of demand and supply as conditioned by substitution and scarcity on the one hand, and the average level of money prices seen as being explained by the supply and demand for money on the other. While classical economists avoided this conflict by distinguishing between real and monetary spheres in an economy, others have followed Wicksell’s lead to restrict monetary economics to the study of disequilibria and adjustment problems. By showing the consistency between Keynes’ General Theory and Hayek’s ‘Economics and Knowledge’, this paper provides a rationale for focusing on monetary controversy outside the ‘Wicksell Connection’. JEL: E40, B22